Development and Update of Guideline-based Quality Indicators in Lung Cancer - Utzig, Martin; Hoffmann, Hans; Reinmuth, Niels; Schütte, Wolfgang; Langer, Thomas; Lobitz, Jessica; Rückher, Johannes; Wesselmann, Simone (TumorDiagnostik & Therapie, 2024)
Background In 2022, an update of the German lung cancer guideline, first published in 2010 and revised in 2018, was released. This article aims to show the process of updating, developing, and implementing guideline-based quality indicators (QI) into the certification system for lung cancer centers (LCC). Methods A multidisciplinary and interprofessional working group revised the guideline QIs from 2018 using the strong recommendations of the guideline update, a systematic review for QIs, and the results of the implemented QIs from LCC. Results For 4 out of 8 indicators from the 2018 guideline, the LCC showed an improved implementation of the requirements in the last 3 years (2018–2020). For 3 indicators, the median of the results was constant at a very high level (≥96% or 100%). Only the “adjuvant cisplatin-based chemotherapy” indicator showed declining values between 2018 and 2020. The target values and plausibility limits were well achieved by LCC. After updating the guideline, one QI from 2018 was not included in the new QI set due to the small denominator population. Based on the new strong recommendations, 8 new QIs were defined. From the QI set of the guideline update, 13 of 15 indicators (7 since 2018 and 6 from 2022 on) were adopted into the certification program. Conclusions The guideline recommendations are implemented by LCC at a high level. The process presented confirms the successful implementation of the so-called quality cycle in oncology. The QIs developed by the German Guideline Program in Oncology (GGPO) are adopted by the certification program. The implementation of the QI is measured in LCC, evaluated by the German Cancer Society (DKG), and reflected back to the GGPO. The “real world” data have led to the deletion of one QI and show a high implementation of most QIs in LCC.
Keywords: lung cancer; quality indicators; key figures; quality of care; guideline